2019
DOI: 10.1007/978-3-030-32692-0_71
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Aware Complementary-Task Learning for Multi-organ Segmentation

Abstract: Multi-organ segmentation in whole-body computed tomography (CT) is a constant pre-processing step which finds its application in organ-specific image retrieval, radiotherapy planning, and interventional image analysis. We address this problem from an organ-specific shapeprior learning perspective. We introduce the idea of complementary-task learning to enforce shape-prior leveraging the existing target labels. We propose two complementary-tasks namely i) distance map regression and ii) contour map detection to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…In other words, we use an architecture, which is very similar to the commonly used 3D U-Net architecture with some modifications [1]. We decide to use U-Net, because this is a very successful architecture for diverse medical imaging tasks [3,5,8,10,11,15]. We refer to our solution as Aν-net, which are homophones of 'Aneu-net' and 'an U-net.'…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, we use an architecture, which is very similar to the commonly used 3D U-Net architecture with some modifications [1]. We decide to use U-Net, because this is a very successful architecture for diverse medical imaging tasks [3,5,8,10,11,15]. We refer to our solution as Aν-net, which are homophones of 'Aneu-net' and 'an U-net.'…”
Section: Methodsmentioning
confidence: 99%
“…Since Dice loss provides an edge at handling class imbalance [8,10] and crossentropy loss is beneficial for smooth training convergence [9,14], we use both. The total loss function of our method is as follows:…”
Section: Methodsmentioning
confidence: 99%
“…IBBM. We use three 2D U-Net 44,[53][54][55] segmentation architectures with some modifications. We implemented the 2D segmentation architecture separately for slices of all three orientations (axial, coronal and sagittal) of the 3D dataset (analogous to Guha Roy et al 56 ).…”
Section: Technical Validationmentioning
confidence: 99%
“…Some studies found superior predictive performances using CNNs compared to handcrafted features [25,26]. Radiomics-based approaches also enable localization and segmentation of volumes of interest (VOI) [27,28].…”
Section: Introductionmentioning
confidence: 99%